From Transnational Policy to National Curricula: Tracing the Diffusion and Integration of Sustainability in School Curricula in Pakistan, Norway, England, and India - Khan, Gulab; Tahirsylaj, Armend; Werler, Tobias Christoph (Nordic Journal of Comparative and International Education (NJCIE), 2025)
This paper examines how transnational policies on sustainability, particularly the UN's Sustainable Development Goals (SDGs), diffuse to and reflect in national curriculum frameworks in England, India, Norway, and Pakistan. Using a qualitative exploratory design, the study analyses policy documents from transnational organisations and national curriculum frameworks from the four countries. The research focuses on how these countries conceptualize and integrate sustainability within their education systems, exploring the dominant educational ideologies underpinning these approaches. The findings reveal a clear pattern of diffusion of the three-dimensional model of sustainability (environmental, social, and economic) from transnational policies to national contexts. However, the study also highlights significant variations in how each country integrates this model, reflecting different national contexts, cultural values, and policy decisions. The study concludes that despite a global push for sustainability education, its integration remains largely contingent on national priorities and contextual factors. Further research is needed to understand how these different approaches translate into classroom practice and impact pupil learning. In particular, the study highlights in comparative terms the interplay of the national and the global in shaping curricular conceptualizations of sustainability and education for sustainable development.